Pengaruh Harga dan Kepercayaan Konsumen Terhadap Keputusan Pembelian UMKM Garasi Hoc Malang - Kusuma, Fahrizha; Lestari, Baroroh; Murtiyanto, Rizky Kurniawan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The increasingly modern development of the coffee business has triggered fierce competition, including among MSME players. Garasi HOC Malang is one MSME that competes through pricing strategies and building customer trust. However, there has been no research examining the influence of these two factors on consumer purchasing decisions. This study aims to analyze the influence of price and consumer trust on purchasing decisions at Garasi HOC Malang SME. This study uses a quantitative approach with explanatory research. Data was collected through an online questionnaire from 100 respondents who had purchased products at Garasi HOC Malang, using purposive sampling techniques. Data analysis was conducted through validity and reliability tests, multiple regression analysis, and classical assumption tests. The results show that, partially, price and consumer trust have a positive and significant effect on purchasing decisions. Simultaneously, both have a significant effect with an F value greater than the F table value. The coefficient of determination indicates that variations in purchase decisions are influenced by price and consumer trust. MSMEs are advised to continue maintaining their pricing strategies and building trust in order to increase consumer purchase decisions.